Eksplorasi Efisiensi Biaya Produksi Usaha Tani Jagung Berbasis Budaya Motiayo Di Desa Huntulohulawa - Inul Hemeto; Tri Handayani Amaliah; Muzdalifah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to explore the level of cost efficiency of corn farming based on Motiayo culture carried out by corn farmers in Huntulohulawa Village. This study uses a Qualitative research method with an Ethnomethodology approach. The data sources used in this study are primary data. Data analysis techniques in this study follow ethnomethodology rules, including data reduction, data presentation, indexicality, reflexivity and drawing conclusions. The results of the study show that with the Motiayo culture, the efficiency of corn farming production costs can be achieved without eliminating the value of togetherness or social values. The production costs of corn farming in Huntulohulawa Village in general are Rp. 9,460,000. With the motiayo culture, farmers do not incur labor costs in the form of wages for workers during the spraying, planting, fertilizing, maintenance, and harvesting processes. So that farmers can save costs of Rp. 3,400,000.